"Embracing what is rightfully ours": representing Australian Aboriginal Brotherboy identities. (2nd January 2020) - Anae, Nicole
ABSTRACT: While transgender people – Sistergirls and Brotherboys – have reportedly been part of Australian Aboriginal/Indigenous and Torres Strait Islander culture long before European colonisation, it is only relatively recently that documentaries and short documentaries (short-docs) have focused specific attention on the Brotherboy community. The term Brotherboy (sometimes "Brothaboy" or "Brotha boy") is used by Australian Aboriginal female-assigned individuals who identify as, and live partly or fully as men. Within a cultural moment tracking the beginnings of a broader visibility of Brotherboys within contemporary Australian film and television programs, this article explores the ways in which the documentary as a form of visual representation not only confronts the discourse of Brotherboy invisibility in terms of self-representation/trans representation, but also how the form itself operates to inform Australian Indigenous communities of the various challenges Brotherboys face in negotiating their transition alongside strictly observed Indigenous cultural practices, and, in many cases strictly held spiritual beliefs in the expression and fashioning of the self.